Socialization of Household Waste Processing into Eco-enzyme Products in Gegutu Reban Hamlet, Dasan Griya Village, West Lombok - Rachmawati Noviana Rahayu; Suripto; Siti Raudhatul Kamali; Supardiono; Baiq Fadila Arlina; Natacha Amalia (Universitas Mataram, 2026)
The problem of household organic waste remains a significant environmental issue in the Lembar region of West Lombok, particularly in Dasan Griya Village, West Lombok. This is characterized by low public awareness of waste management and minimal knowledge and skills in processing organic waste into products with higher economic value. This activity was carried out with the aim of increasing the motivation, knowledge and skills of the community in processing kitchen waste into ecoenzyme liquid soap. Socialization activities were carried out using lecture, discussion, demonstration and practice methods with housewives and teenagers as participants, facilitated by the local government. The results showed that the participants were very enthusiastic, and the knowledge and skills of most participants regarding processing kitchen waste into ecoenzyme liquid soap increased. The activity material absorbed by the participants includes a sustainable community-based waste management system and the fermentation-based kitchen waste processing into ecoenzyme products with high economic value.The participants expressed their readiness to further practice processing kitchen waste into ecoenzyme soap products at home.